2009
DOI: 10.1073/pnas.0811632106
|View full text |Cite
|
Sign up to set email alerts
|

A differentiation pathway for B1 cells in adult bone marrow

Abstract: The recent description of a Lin ؊ AA4.1 ؉ CD19 ؉ B220 Lo/؊ B1-specified progenitor (B1P) population in adult marrow adds support for the argument that these unique B cells arise from a distinct lineage. However, the origins of B1P were not investigated and their developmental relationships to conventional B2 cells remain unclear. We now report that B1P development is IL-7R␣-dependent, and negatively regulated by Bruton tyrosine kinase. Lymphoid characteristics of B1P were further studied with recombination act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
98
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(106 citation statements)
references
References 45 publications
7
98
0
1
Order By: Relevance
“…Of particular note are recent reports showing the development of B-1 cells from adult hematopoietic stem cells (HSCs) and common lymphoid progenitors (CLPs) (22)(23)(24)(25). The concomitant production of B-1 and B-2 cells from adult CLPs, defined as B lineage-specified progenitors from which surface IgM + B cells derive (26), also links the development of these two B-cell populations.…”
mentioning
confidence: 99%
“…Of particular note are recent reports showing the development of B-1 cells from adult hematopoietic stem cells (HSCs) and common lymphoid progenitors (CLPs) (22)(23)(24)(25). The concomitant production of B-1 and B-2 cells from adult CLPs, defined as B lineage-specified progenitors from which surface IgM + B cells derive (26), also links the development of these two B-cell populations.…”
mentioning
confidence: 99%
“…These findings, which provided some of the earliest evidence of lineage distinctions between B-1 and B-2 cells, also showed that some B-1 progenitors persist in adults. However, discussions of whether the BM-derived B-1 cells arose from independent progenitors or from developmental diversion of B-2 cells pushed the entire issue into the realm of experts, from whence it has only now been rescued by the recognition of distinct embryonic progenitors for B-1 and B-2 (1) and of a small subset of phenotypically distinct B-1 progenitors in adult BM (7)(8)(9).…”
mentioning
confidence: 99%
“…The B1-specified progenitors were found not only in fetal liver but also in BM of adult mice (9,24). We evaluated the B1-specified progenitors in the BM of WT and VAD mice but could not distinguish a distinct population of CD19 + B220 low/− cells in Lin − AA4.1 + gate (Fig.…”
Section: Resultsmentioning
confidence: 99%